Fatigue Life Evaluation of Suspension Knuckle Using Multibody Simulation Technique - M., Kamal; M. M., Rahman; Abdul Ghaffar, Abdul Rahman (Faculty Mechanical Engineering, UMP, 2012)
Suspension is part of automotive systems, providing both vehicle control and passenger comfort. The knuckle is an important part within the suspension system, constantly encountering the cyclic loads subjecting it to fatigue failure. This paper presents an evaluation of the fatigue characteristics of a knuckle using multibody simulation (MBS) techniques. Load time history extracted from the MBS is used for stress analysis. An actual road profile of road bumps was used as the input to MBS. The stress fluctuations for fatigue simulations are considered with the road profile. The strain-life method is utilized to assess the fatigue life. The instantaneous stress distributions and maximum principal stress are used for fatigue life predictions. Mesh sensitivity analysis has been performed. The results show that the steering link in the knuckle is found to be the most susceptible region for fatigue failure. The number of times the knuckle can manage a road bump at 40 km/hr is determined to be approximately 371 times with a 50% certainty of survival. The proposed method of using the loading time history extracted from MBS simulation for fatigue life estimation is found to be very promising for the accurate evaluation of the performance of suspension system components.